2004
DOI: 10.1159/000078561
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism for an ectopic NOR at 8pter and a complex rearrangement of chromosome 8 in a patient with severe psychomotor retardation

Abstract: We describe a 3-year-old girl with severe delays in mental and motor skills, a history of generalized seizures, and subtle dysmorphic features. Conventional cytogenetics revealed a mosaic karyotype. A de novo ectopic NOR at the telomeric region of the short arm of one chromosome 8 (8ps) was found in 90% of lymphocyte and in 98% of fibroblast metaphases. A small NOR-bearing marker chromosome and a large derivative chromosome 8 without short arm satellites (der(8)) were present in the remaining cells. FISH with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although the Utype exchange (mechanism 3) is the most frequent inv dup del mechanism in all other chromosome arms [Rowe et al, 2009], the majority of reported inv dup del(8p) can be explained by the mechanisms 1 or 2 mentioned above ( fig. 4 ; table 3 ) [Weleber et al, 1976;Dill et al, 1987;Minelli et al, 1993;Barber et al, 1994;de Die-Smulders et al, 1995;Guo et al, 1995;Floridia et al, 1996;Macmillin et al, 2000;Giglio et al, 2001;Pabst et al, 2003;Felbor et al, 2004;Shimokawa et al, 2004Shimokawa et al, , 2005Cooke et al, 2008;Zuffardi et al, 2009] with few exceptions [Buysse et al, 2009;Rowe et al, 2009]. In this study, the formation of the inv dup del(8p) appears to be caused by mechanism 2 in patient 2, and by mechanism 3 in patient 3 ( fig.…”
Section: Discussionmentioning
confidence: 51%
“…Although the Utype exchange (mechanism 3) is the most frequent inv dup del mechanism in all other chromosome arms [Rowe et al, 2009], the majority of reported inv dup del(8p) can be explained by the mechanisms 1 or 2 mentioned above ( fig. 4 ; table 3 ) [Weleber et al, 1976;Dill et al, 1987;Minelli et al, 1993;Barber et al, 1994;de Die-Smulders et al, 1995;Guo et al, 1995;Floridia et al, 1996;Macmillin et al, 2000;Giglio et al, 2001;Pabst et al, 2003;Felbor et al, 2004;Shimokawa et al, 2004Shimokawa et al, , 2005Cooke et al, 2008;Zuffardi et al, 2009] with few exceptions [Buysse et al, 2009;Rowe et al, 2009]. In this study, the formation of the inv dup del(8p) appears to be caused by mechanism 2 in patient 2, and by mechanism 3 in patient 3 ( fig.…”
Section: Discussionmentioning
confidence: 51%
“…[2][3][4][5][6] These REPD-and/or REPP-related 8p genomic rearrangements include (1) the 8p23.1 deletion or duplication between REPD and REPP, [6][7][8][9] (2) the 8p23.1 paracentric inversion between REPD and REPP, 8,10 (3) the pericentric inversion (inv(8)(p23.1q22.1)) and recombinant chromosome 8 (rec (8)dup(8q)inv(8)(p23.1q22.1)), 11 (4) the 8p interstitial inverted duplication with associated terminal deletion (inv dup del(8p)), 5,6,8,10,[12][13][14][15][16][17][18][19][20][21][22][23][24] (5) the 8p translocations involving the 8p23.1, 25,26 and (6) different types of supernumerary chromosome 8 (SMC (8)) involving the breakpoints within 8p23.1. 4,27 In addition to these defined 8p genomic abnormalities, other pathogenic genomic changes have been identified, [28][29][30] whereas numerous genomic imbalances on 8p are still described as copy number variants (CNVs) of unknown clinical significance or CNVs without apparent clinical significance (benign CNVs) (http://projects.tcag.ca/variation).…”
Section: Introductionmentioning
confidence: 99%